Governance and Security Challenges in Nigeria: The Bane of Development - Isaac, John; Istifanus, Kuden Plangkat; Emmanuel, Datuhul Domshak (Kashere Journal of Politics and International Relations, 2025)
In the 21st century, Nigeria continue facing myriads of challenges in the area of governance; ranging from lopsided policy initiations and inadequate will for policy implementation. This issue has negatively affected Nigeria’s bid towards national development. The hope of most Nigerians on the use of state power for a sustainable socio-economic transformation in the 21st century has been dashed. It is on this note that the study focuses on the challenges of governance and national development in Nigeria, with reference to 21st century. The methodology is both descriptive and analytical. The study reveals that bad governance in Nigeria remains a bane to national development in all spheres of life. The paper argues that much of government’s development initiatives have remained elitist, bias to development, unfocused and have failed to significantly impact positively on the generality of people who are the main target of development. The paper recommends a fundamental change in the country’s governance in order to arrest the bottlenecks that have militated against national development in Nigeria.